Basic cell culture - edited by J.M. Davis (Oxford University Press, 2002)
The use of animal, including human, cell culture has expanded enormously during the last twenty years, with the new applications appearing all the time. This book guides the newcomer progressively through all those areas which are basic to the performance of cell culture. It will also prove useful to the experienced worker entering a new field or setting up a new laboratroy, and as a source of reference on basic techniques. The topics covered include setting up and equipping a cell culture laboratory, sterilization of fluids and equipment, culture media, basic culture technique and the maintenance of cell lines, primary culture and the isolation of new cell lines, specific cell types and their requirements, single cell cloning, quality control of cell lines and the prevention, detection, and cure of contamination